2015
DOI: 10.1038/cddis.2015.277
|View full text |Cite
|
Sign up to set email alerts
|

K+ regulates Ca2+ to drive inflammasome signaling: dynamic visualization of ion flux in live cells

Abstract: P2X7 purinergic receptor engagement with extracellular ATP induces transmembrane potassium and calcium flux resulting in assembly of the NLRP3 inflammasome in LPS-primed macrophages. The role of potassium and calcium in inflammasome regulation is not well understood, largely due to limitations in existing methods for interrogating potassium in real time. The use of KS6, a novel sensor for selective and sensitive dynamic visualization of intracellular potassium flux in live cells, multiplexed with the intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(118 citation statements)
references
References 43 publications
2
104
0
1
Order By: Relevance
“…Binding of ATP to P2X7 results in the influx of Na + and Ca 2+ ions with simultaneous K + efflux. Importantly, this has been shown to elicit activation of the NLRP3 inflammasome in LPS-stimulated macrophages , which causes secretion of IL-18 (but also of the pro-inflammatory cytokine IL-1β) and may thus promote maintenance and function of the epithelial barrier (Mariathasan et al, 2006; Sutterwala et al, 2014; 2006; Yaron et al, 2015). Long-term activation of P2X7, however, results in formation of a large membrane pore and cell death (Nuttle and Dubyak, 1994; Smart et al, 2003).…”
Section: Microbiome-associated Metabolites That Shape the Immune Systemmentioning
confidence: 99%
“…Binding of ATP to P2X7 results in the influx of Na + and Ca 2+ ions with simultaneous K + efflux. Importantly, this has been shown to elicit activation of the NLRP3 inflammasome in LPS-stimulated macrophages , which causes secretion of IL-18 (but also of the pro-inflammatory cytokine IL-1β) and may thus promote maintenance and function of the epithelial barrier (Mariathasan et al, 2006; Sutterwala et al, 2014; 2006; Yaron et al, 2015). Long-term activation of P2X7, however, results in formation of a large membrane pore and cell death (Nuttle and Dubyak, 1994; Smart et al, 2003).…”
Section: Microbiome-associated Metabolites That Shape the Immune Systemmentioning
confidence: 99%
“…The NLRP3 inflammasome comprises (a) NLRP3, (b) an apoptosis-associated speck-like protein containing a caspase activation recruitment domain (ASC), and (c) procaspase-1. In response to a wide range of danger signals, including oxygen-free radicals, K + efflux, or mitochondrial stress [68], NLRP3 recruits the adaptor protein ASC which in turn interacts with procaspase-1. Inflammasome oligomerization promotes the autocatalytic activation of procaspase-1 and the processing of prointerleukin- (IL-) 1 β [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our experiments showed that the Ca 2+ chelator, BAPTA-AM, did not completely inhibit caspase-1 activation and mitochondrial ROS production. Ca 2+ may have a direct activating effect on NLRP3 inflammasome [11], [16], [17], [18], [19]. Therefore, a parallel pathway of Ca 2+ activation of the NLRP3 inflammasome cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The most characterized inflammasome is the NLRP3 inflammasome, which is composed of a sensing apparatus (NOD-like receptor pyrin domain 3, NLRP3), an adaptor (apoptosis-associated speck-like protein containing a caspase recruitment domain, ASC) and the pro-form of cytokine converting enzyme (pro-caspase-1) [7]. Numerous structurally diverse stimulators activate the NLRP3 inflammasome through different signaling pathways, including K + efflux [7], [8], [9], [10], [11], reactive oxygen species (ROS) production [12], [13], [14], [15], Ca 2+ mobilization [11], [16], [17], [18], [19], mitochondrial destabilization [17], [20], [21], [22], [23], and lysosome rupture [24], [25]. Therefore, it is critical that the molecular mechanisms by which novel stimulators activate the NLRP3 inflammasome are delineated in a context-specific manner.…”
Section: Introductionmentioning
confidence: 99%